The Eucharist and ecumenism: let us keep the feast - Hunsinger, George (Current issues in theology, 2008)
The bread that we break: controversies -- The iron in the fire: a proposal -- The sacrifice we offer: controversies -- Christ our Passover: a proposal -- Eucharistic ministry: controversies -- Eucharistic ministry: an impending impasse? -- The Eucharistic transformation of culture -- Nicene Christianity, the Eucharist, and peace -- Conclusion: let us keep the feast